EFFECTS OF AZOTOBACTER INOCULATION ON THE GROWTH AND PRODUCTIVITY OF SWEET CORN (ZEA MAYS L. VAR. SACCHARATA STURTEV.) IN GREEN HOUSE - ENDANG ROSMAYANI (NIM 20604015), HERTI
Sweet corn (Zea mays L. var. saccharata Sturtev) is one of the economically potential agricultural commodities. The main lost component in sweet corn production is on fertilizer. Its extensive use has been inflicting an adverse effect on environment causing pollution of drinking water. The application of nitrogen fixing micro organism as bio fertilizer is a good alternative solution. Azotobacter is one of micro organisms, which has the ability to fix nitrogen. The experiment was conducted to evaluate the effect of Azotobacter inoculants on the yield of sweet corn, whether it can reduce the use of nitrogen chemical fertilizer and to find out which is the best combination of inoculants and chemical fertilizer that give the best result. The experiment consists of (1) Isolation (2) Screening (3) Identification (4) Treatment. The experiment was conducted in a completely randomized design with 6 treatments and 2 controls (negative and positive). Twelve isolates of Azotobacter species were obtained at the first step. Two isolates were chosen at the second step which were identified in third step as Azotobacter beijeranckii and Azotobacter chroococcum. The fourth step shows that treatment P5 (Azotobacter chroococcum + 25% urea) gives the highest result in plant height, corn fresh weight and shoot dry weight, which differs significantly from negative control (without bacteria and urea) and positive control (without bacteria and 100% dose of urea). The highest number of leaves is achieved in treatment P5 and P6 (Azotobacter chroococcum + 50% urea) which differ significantly from negative control but not with positive control and other treatments. Highest root dry weight is obtained by treatment P3 (Azotobacter beijeranckii + 50% urea), P4 (A. chroococcum), P5 and P6 which do not differ significantly from P1 (A. beijerinckii) and P2 (A. beijerinckii + 25% urea) but they differ significantly from negative and positive controls. Enzyme activity test shows that all treatments are significantly different from negative and positive controls. The highest ammonia content in soil is reached by treatments P5 and P6 which differ significantly from negative control. Nitrate content in soil of all treatments do not differ significantly with negative and positive controls. Pearson correlation test shows that there are positive correlations among plant height, corn fresh weight, shoot and root dry weight with enzyme activity and ammonia content. Nitrate content in soil shows negative correlation with all parameters. The conclusion of this experiment is that the inoculation of Azotobacter chroococcum give positive effects on the growth of sweet corn and it reduces the use of chemical fertilizer. The best combination of inoculums and chemical fertilizer is treatment P5 (A. chroococcum+25% urea) which gives the best result in plant height, corn fresh weight and shoot dry weight.